UKURAN PERUSAHAAN SEBAGAI PEMODERASI PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR ASET TERHADAP STRUKTUR MODAL - Reina Angreani; Lukman Suryadi (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This study aims to determine the effect of profitability, liquidity, and asset structure on capital structure with company size as a moderating variable in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for a 4-year period from 2018 to 2021. Methods The technique used in this research is the purposive sampling method selection technique with a total sample of 208 data consisting of 52 companies. The data processing technique uses multiple linear regression analysis which is processed with the Eviews 12.0 application and Microsoft Office 365 Excel. The research results show that the variables of profitability and liquidity have a negative effect on capital structure and asset structure have a positive effect on capital structure. The moderating variable, namely company size, is unable to moderate the influence of the three financial factors (profitability, liquidity, and asset structure) on capital structure. The implication of this research is the importance of company management to know and pay attention to the factors that can affect the capital structure with the aim of achieving optimal capital structure.